Six-minute walking distance in healthy Chinese people older than 60 years - He Zou (BMC Pulmonary Medicine, 2020)
Abstract Background The six-minute walking test (6MWT) is a tool that plays a key role in evaluating the functional exercise capacity, prognosis and evaluation of treatment response of patients with various cardiopulmonary diseases. However, standard reference equations are currently unavailable for the six-minute walking distance (6MWD) for people aged 60–85 years in China. The purpose of this study was to 1) measure the 6MWD of healthy Chinese people aged 60–85 years, 2) establish reference equations for predicting the 6MWD, and 3) compare our reference equations with equations reported in previously published studies. Method We obtained informed consent from each participant prior to the test, and the research design was approved by the Ethics Committee of Wenzhou People’s Hospital. The demographic and anthropometric data and the 6MWD of healthy Chinese subjects aged 60–85 years old were measured using a standardized protocol. Every subject completed two 6MWTs, and the longest 6MWD further analyzed. Results Two hundred sixty-six subjects (128 males and 138 females) completed the 6MWT, and the mean walking distance was 518 ± 72 m. Males achieved a longer walking distance than females (518 ± 72 m vs. 487 ± 70 m; p < 0.0001), and active subjects achieved a longer walking distance than nonactive subjects (512 ± 76 m vs. 485 ± 63 m; p < 0.0001). According to the univariate analysis, the 6MWD was significantly associated with age, height, body mass index (BMI), heart rate and blood pressure after exercise and changes in heart rate before and after exercise. The stepwise multivariate regression analysis identified age, height and BMI as independent predictors of the 6MWD. The reference equations for Caucasians and South Americans tended to overestimate the 6MWD of our subjects, while the equations for Asian and African populations tended to underestimate the 6MWD. Conclusions This study is the first to describe the 6MWD of healthy Chinese people aged 60–85 years, and reference prediction equations were proposed. These findings will help to improve the evaluation of Chinese patients with diseases that affect exercise capacity.